Effects of Additive Intercropping on Mineral Uptake of Onion and Fenugreek at Different Densities - Tahereh Moghbeli; Sahebali Bolandnazar; Jabber Panahandeh; Yaegoob Raei (Journal of Agricultural Sciences)
Increasing world population demands for food, limited natural resources have created the risk of food security for current and future generations. Intercropping is regarded as an effective strategy in sustainable agriculture. Therefore, current study was carried out to evaluate the nutrient uptake of onion and fenugreek intercropping system during two growing season of (2015-2016 and 2016-2017) at a research field in Kerman, Iran. Two factorial experiments based on completely random blocks design with three replications were carried out. The treatments in this study were including: onion densities as the first factor (30, 25 and 20 plants m-2) and fenugreek densities as the second factor at three levels of 25, 15 and 12 plants m-2 with sole cropping of two species at these densities. Results showed that in the both ofyears, mineral concentration and uptake (N, P and K) of onion leaf and bulb and fenugreek in intercropping increased in comparison with mono cropping for two species. In both years, the highest and lowest nutrient content of onion was observed in the densities of 30 and 20 plant m-2. In general, it can be said that intercropping systems have some positive effects on nutrient content and uptake of onion.